Proclamation (Raton, NM Raton Range, 1997)
Article is about the Art and Humanities council receiving a proclamation from the city.
Newspaper article + Photograph of Barbara Carlini, Colleen Grogan, Danl Allen and Mayor Joe Apache.
Master list item #: 97
File location is in the Raton file Cabinet
Keywords: Carlini, Barbara -- Art and Humanities Council Member; Grogan, Colleen -- Art and Humanities Council Member; Allen, Danl -- Art and Humanities Council Member; Apache, Joe -- City of Raton Mayor; National Arts and Humanities Month; Proclamations; Art and Humanities Council; Raton, New Mexico